Phospholipase A2, prostaglandin E2 and polyunsaturated fatty acid metabolic abnormalities in multiple sclerosis. Issue 3 (December 2013) - Hon, Gloudina M.; Erasmus, Rajiv T.; Matsha, Tandi E.
Abstract Aim Metabolic abnormalities reported in patients with multiple sclerosis include a decrease in cell membrane fatty acid C20:4n‐6. The aim of the present study was to investigate whether this decrease was associated with abnormalities in the prostaglandin E2 pathway in patients with multiple sclerosis. Methods The study population included 31 patients with multiple sclerosis and 30 healthy controls. Peripheral blood mononuclear cell membrane fatty acids were measured by gas chromatography, secretory‐phospholipase A2, and prostaglandin E2 with enzyme‐linked immunosorbent assays and C‐reactive protein with a Beckman auto‐analyser. Results Prostaglandin E2 was increased in patients (545.5 pg/mL; quartile range 585.1 pg/mL) and controls (248.2 pg/mL; quartile range 183.6 pg/mL; P = 0.0018). Phospholipase A2 was inversely associated with C20:4n‐6 in patients and controls, respectively (P = 0.0398 and P = 0.0182). C‐reactive protein showed a positive association with phospholipase A2 in patients (P = 0.0006), and an inverse association with prostaglandin E2 in controls (P = 0.0006). Conclusions The increase in prostaglandin E2 concentration in plasma from patients with multiple sclerosis was possibly enhanced by the positive association between the C‐reactive protein and phospholipase A2 concentrations present in patients; that is, active stimulation of the prostaglandin E2 pathway, which can possibly explain decreases in membrane n‐6 fatty acid C20:4n‐6 reported in cell membranes from patients. It is not clear from the results of the present study whether this denotes chronic inflammation in patients, but could be expected to contribute to central nervous system damage reported in patients with multiple sclerosis.